EFFECTIVENESS OF MICROFINANCE BANK INITIATIVES IN PROMOTING SUSTAINABLE LIVELIHOOD PRACTICES AMONG FARMERS IN KWARA STATE, NIGERIA - Olayinka Jelil Yusuf; L.K Olatinwo; Z.T Saka; M.J Wahab; I.A Akintola (Malete Journal of Accounting and Finance)
The low-income poor rural entrepreneurs, farmers inclusive, are often excluded from conventional bank benefits in terms of access to financial initiatives. The introduction of microfinance banks across Nigeria by the Government was to enhance financial inclusion to cater to these vulnerable groups. This study, thus, aimed to assess the effectiveness of microfinance bank (MFB) initiatives in promoting sustainable livelihood practices among rural communities in Kwara State, Nigeria. A cross-sectional research design method was used to select 143 farmers following a multistage sampling procedure. Primary data were collected with structured interview schedule and analyzed using descriptive statistics and regression analysis. Results revealed that 61.0% of the farmers were males, educated (61.0%), with mean age of 34 years. The results also revealed that MFBs played a significant role in providing capacity-building and support services (Mean Score=4.23) which ranked highest in their effectiveness, while increase access to credit and small business was ranked least (MS=3.27). The findings further reveal that limited outreach and accessibility and insufficient long-term funding and investment were the most ranked challenges by the farmers in the study area. The regression analysis further highlighted that education (β = 0.273, p = 0.002) and marital status (β = -0.285, p = 0.003) significantly influenced the impact of rural finance, emphasizing the role of socioeconomic factors in shaping financial outcomes. The study concluded that improving outreach, tailoring financial products, enhancing financial literacy, and addressing infrastructure gaps could ameliorate the constraints facing rural finance programs in supporting sustainable livelihoods. The study therefore recommends the expansion of MFB services to expand outreach and enhancing financial literacy programs to maximize the benefits of these initiatives.